Menelaah Kembali Peran Maṣlaḥah sebagai Sumber, Metode, dan Tujuan Hukum Islam - Lubis, Alwi Ibrahim; Harahap, Anri Habibi; Hasanah, Uswatun (Program Studi Hukum Ekonomi Syariah, 2026)
Maṣlaḥah constitutes a fundamental principle in Islamic law, functioning not only as a legal objective but also as a source and method of legal reasoning. This article revisits the concept of maṣlaḥah, with particular attention to maṣlaḥah mursalah as a basis for ijtihād in situations where no explicit textual evidence is available, and examines its relationship with maqāṣid al-syarī’ah. Through an analytical review of the thought of classical and modern scholars such as al-Ghazali, Abd al-Wahhab Khallaf, and Najm al-Din al-Thufi, this study demonstrates a spectrum of approaches to maṣlaḥah, ranging from restrictive to more progressive interpretations. Furthermore, the classification of maṣlaḥah into three levels: ḍarūriyyah, ḥājiyyah, and taḥsīniyyah, highlights its crucial role in maintaining the relevance, flexibility, and normative orientation of Islamic law amid social change. This article argues that maṣlaḥah is not merely a complementary element in Islamic legal theory, but a central instrument in realizing public welfare and safeguarding the higher objectives of the sharia.